Continuous Transformation and Neo-Carbon Energy Scenarios - Sirkka Heinonen; Nicolas Balcom Raleigh (Finland Futures Research Centre, 2022)
This report describes the process and results of Futures Clinique held 22nd May 2015 at Aalto University. At the Futures Clinique − titled Creatively Sustainable Built Environment in Neo-Carbon Energy Worlds − students of Continuous Transformation Course elaborated four tentative scenarios of an on-going Tekes-funded project called Neo-Carbon Energy. The goal of the research project is to explore futures based on renewable energy system. The report begins by describing the method, project, and the theoretical framework. This is followed by the description of the process and results of the Futures Clinique. The nature of change and transformation is also discussed. Working in four groups, the participants focused on a chosen scenario through a multi-staged process. As the report is given to the participants for feedback as well as for further discussion and development, comments on the results are also presented. The conclusive chapter presents observations on transformation and futures learning.